GENETIC VARIABILITIES OF AGRONOMIC TRAITS AND BACTERIAL LEAF BLIGHT RESISTANCE OF HIGH YIELDING RICE VARIETIES - Nafisah Nafisah; Celvia Roza; Nani Yunani; Aris Hairmansis; Tita Rostiati; Ali Jamil (Indonesian Agency for Agricultural Research and Development, 2019)
Hundred of high yielding and bacterial leaf blight (Xanthomonas oryzae pv. oryzae, Xoo) resistant rice varieties released since the 1960s are important sources of genetic materials for exploring superior genotypes. The study aimed to evaluate the genetic resistance of 177 rice varieties to Xoo and their agronomic traits. The evaluations were conducted at the Indonesian Center for Rice Research Experimental Station during the wet season (December 2015-March 2016). The bacterial leaf blight resistance was evaluated for Xoo pathotypes III, IV, and VIII using the clipping method. The genetic variation among genotypes was categorized as low (0–10%), medium (10–20%), and high (>20%), whereas the heritability was categorized as low (0-30%), medium (30-60%), and high (>60%). The variability of resistance to Xoo pathotypes, grain yield, and spikelet fertility was low, while the variability of plant height, productive tiller number, filled grain, and total spikelet was medium, and the variability of unfilled grain number was high. The 29 varieties were categorized as superior based on their agronomic traits or resistance to Xoo pathotypes. In conclusion, Batutegi and Fatmawati were superior in the total spikelet number, while Rojolele and Inpari 2 were supreme in the thousand-grain weight. Dodokan had a very short maturity, and Inpari 24, Conde, Kalimas, Angke, Inpari 17, and Inpara 8 had the highest resistance to Xoo pathotypes. The study implies that the identified rice superior genotypes could be used as genetic materials to design cross combinations for higher yield potential and BLB resistance varietal improvement.